An examination of college student wellness: A research and liberal arts perspective. Issue 2 (July 2017) - Baldwin, Debora R; Towler, Kerry; Oliver, Michael D; Datta, Subimal
Promoting wellness within academia reduces disease frequency and enhances overall health. This study examined wellness factors among undergraduate students attending a research university ( n = 85) or a small liberal arts college ( n = 126). Participants were administered surveys which measured physical, emotional, social, intellectual, and occupational wellness. Significant institutional differences emerged on measures of physical and social wellness. When collapsed across academic institutions, students who were gainfully employed reported greater self-efficacy compared with unemployed students. Gender differences emerged on measures of physical and social well-being. Our findings support the need for targeted interventions that facilitate enhanced college student development and well-being.